Enhancement of Methacholine-Evoked Tracheal Contraction Induced by Bacterial Lipopolysaccharides Depends on Epithelium and Tumor Necrosis Factor. (11th March 2012) - Secher, T.; Rodrigues Coelho, F.; Noulin, N.; Lino dos Santos Franco, A.; Quesniaux, V.; Lignon, J.; Mitchell, J.; Moser, R.; Gomes, E.; Mirotti, L.; Tavares-de-Lima, W.; Ryffel, B.; et al.
Abstract : Inhaled bacterial lipopolysaccharides (LPSs) induce an acute tumour necrosis factor-alpha (TNF- α -) dependent inflammatory response in the murine airways mediated by Toll-like receptor 4 (TLR4) via the myeloid differentiation MyD88 adaptor protein pathway. However, the contractile response of the bronchial smooth muscle and the role of endogenous TNF α in this process have been elusive. We determined the in vivo respiratory pattern of C57BL/6 mice after intranasal LPS administration with or without the presence of increasing doses of methacholine (MCh). We found that LPS administration altered the basal and MCh-evoked respiratory pattern that peaked at 90 min and decreased thereafter in the next 48 h, reaching basal levels 7 days later. We investigated in controlled ex vivo condition the isometric contraction of isolated tracheal rings in response to MCh cholinergic stimulation. We observed that preincubation of the tracheal rings with LPS for 90 min enhanced the subsequent MCh-induced contractile response (hyperreactivity), which was prevented by prior neutralization of TNF α with a specific antibody. Furthermore, hyperreactivity induced by LPS depended on an intact epithelium, whereas hyperreactivity induced by TNF α was well maintained in the absence of epithelium. Finally, the enhanced contractile response to MCh induced by LPS when compared with control mice was not observed in tracheal rings from TLR4- or TNF- or TNF-receptor-deficient mice. We conclude that bacterial endotoxin-mediated hyperreactivity of isolated tracheal rings to MCh depends upon TLR4 integrity that signals the activation of epithelium, which release endogenous TNF α .